Probing isomers of the benzene dication in a low-temperature trap - Jašík, Juraj; Gerlich, Dieter; Roithová, Jana (Journal of the American Chemical Society, 2014)
The structure of doubly ionized benzene has been spectroscopically studied for the first time. Helium-tagged complexes were prepared at temperatures below 4 K and analyzed using infrared predissociation spectroscopy. Double ionization of benzene yields primarily high-energy dications with a six-membered-ring structure. Some of the dications undergo rearrangement to a more stable pyramidal isomer with a C5H5 base and CH at the apex. By means of isomer-selective heating by a CO2 laser, infrared predissociation spectra of both the classical and pyramidal dications were obtained.